Redo DAIR: The Game Is Seldom Worth the Candle - Ignacio Sancho; Iñaki Otermin-Maya; Jorge Gutiérrez-Dubois; Ignacio Aláez; Julián Librero; Maria Eugenia Portillo; Ángel Hidalgo-Ovejero (MDPI AG, 2022)
Debridement, antibiotics and implant retention (DAIR) remains a commonly utilized technique in the treatment of acute prosthetic joint infections despite its inconsistent outcomes. The performance of a second DAIR after a failed first debridement is controversial as outcomes are uncertain and the final prognosis in the event of failure may be unfavorable. This study analyzes 84 cases of acute prosthetic (hip & knee) joint infection treated with DAIR between 2011 and 2020 at the same institution. In 12 failed cases, a second DAIR was performed, whose success rate was significantly lower than that of the first procedure (8% [95% CI, 0-38] vs. 57% [46-68]). Moreover, the ultimate outcome of the second failed DAIRs was unfavorable with eradication of the infection being achieved in none of the patients. Due to the high likelihood of failure and the potentially grim final prognosis following a second debridement, removal of the components should be considered.